2018
DOI: 10.1111/petr.13184
|View full text |Cite
|
Sign up to set email alerts
|

Biliary drainage as treatment for allograft steatosis following liver transplantation for PFIC‐1 disease: A single‐center experience

Abstract: Development of macrovesicular steatosis post-LT in patients with PFIC-1 is increasingly being observed, with the etiology not fully understood. We highlight successful and effective EBD for reversal of allograft steatosis in 2 patients with PFIC-1 disease and discuss our experience with internal biliary diversion in this patient population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 23 publications
0
27
0
Order By: Relevance
“…13,14 Owing to the resulting colonic reflux, attempts at reversing the stoma have been met with failures. 15 While total external biliary diversion may be better at achieving complete biliary diversion, TIBD is more acceptable to the patients and is associated with a better quality of life. Mali et al showed that TIBD performed at the time of LT could abrogate the diarrhea and steatosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…13,14 Owing to the resulting colonic reflux, attempts at reversing the stoma have been met with failures. 15 While total external biliary diversion may be better at achieving complete biliary diversion, TIBD is more acceptable to the patients and is associated with a better quality of life. Mali et al showed that TIBD performed at the time of LT could abrogate the diarrhea and steatosis.…”
Section: Discussionmentioning
confidence: 99%
“…To avoid the risk of colonic reflux and cholangitis, the isolated jejunal segment is left long (approximately 30 cm). 15 There, however, remains the risk of malnutrition due to nonabsorption of fat-soluble vitamins due to TIBD. These children will therefore need replacement of these nutrients.…”
Section: Discussionmentioning
confidence: 99%
“…Several subsequent reports showed outstanding outcomes of post-transplant biliary diversion, with relief of diarrhea and regression of liver steatosis ( Table 3 ). Some authors described good results of internal biliary diversion used preemptively at the time of LT as a stoma-free procedure to prevent postoperative graft steatosis or as a next step after PEBD [ 9 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Unlike PFIC-2, PFIC-1 is multiorgan disorder due to the broad tissue distribution of FIC1 expression [ 1 , 2 ]. Extrahepatic symptoms, such as diarrhea, pancreatitis, deafness, and poor growth may persist, develop, or aggravate after liver transplantation (LTx) [ 3 9 ]. Moreover, the presence of steatohepatitis progressing to cirrhosis and the need for re-transplantation may be observed after LTx [ 3 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Total biliary diversion involves diverting all the bile flow from the common bile duct to the exterior through a jejunal loop. It is usually reserved for pruritus refractory to PEBD or to prevent and treat allograft steatosis in post LT PFIC1[ 56 ]. Irrespective of the technique used, biliary diversion surgeries lead to a decrease in the concentration of BA, improvement in pruritus score, growth spurt, histological improvement and even reversal of fibrosis in some cases[ 38 , 47 ].…”
Section: Therapeutic Strategies For Pficmentioning
confidence: 99%